The role of subsidies in stabilising farm income: Evidence from Estonia - Aleksandrova, Olha; Zhmykhova, Tetiana; Viira, Ants-Hannes (Agricultural and Food Science, 2022)
This study examines the role of agricultural subsidies in the farm income (FI) variation in Estonia in the period 2006–2019 using data from a balanced panel of Farm Accountancy Data Network (FADN) farms. FI variability is decomposed to three components: market income, total subsidies, and the cost of external factors. The results reveal that subsidies have a larger share in income of smaller farms. Variability of FI differs in farm size quartiles and is significantly lower in case of largest 25% of farms. Revenues are the largest source of variation of FI. While subsidies reduce FI variation, there is no evidence that they are counter-cyclical. We argue that in addition to subsidies, smaller farms need advice on farm management to increase market income, improve its stability, and expand farm size, as larger farms have more stable incomes despite relatively lower producer support estimate (PSE) levels.